The Effect of Intrinsic and Extrinsic Motivation on The Academic Achievement of Students of The Faculty of Economics and Business Uniraya - Anastasia Manao; Meilina Gee; Elnis Anastasia Hondro; Prisensi Gustriani Gee; Wetinaria Laia; Eric Bernadus Bohalima; Lusius Gunawan Franky Saddiman Laia (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study aims to examine the effect of intrinsic motivation and extrinsic motivation on the academic achievement of students at the Faculty of Economics and Business (FEB) UNIRAYA. The study employed a quantitative approach with an associative research design. The population and sample consisted of all 30 students of FEB UNIRAYA. Primary data were collected through questionnaires distributed to all respondents. Data analysis techniques included multiple linear regression analysis, partial t-tests, coefficient of determination (R²), and Pearson correlation analysis, processed using SPSS version 22. The results indicate that intrinsic motivation has a positive and significant effect on students’ academic achievement, while extrinsic motivation does not have a significant partial effect. However, intrinsic and extrinsic motivation simultaneously have a very strong influence on academic achievement, as reflected by an R² value of 0.995. Pearson correlation analysis also reveals a very strong and positive relationship between both types of motivation and academic achievement. These findings confirm that intrinsic motivation plays a dominant role in enhancing students’ academic performance, whereas extrinsic motivation functions as a complementary factor. The study highlights the importance of fostering intrinsic motivation to achieve sustainable academic success in higher education.